PKA‐mediated phosphorylation of Dexras1 suppresses iron trafficking by inhibiting S‐nitrosylation. Issue 20 (7th September 2015) - Chen, Yong; Mathias, Lauren; Falero-Perez, Juliana M.; Kim, Sangwon F.
Abstract : Dexras1 is a small GTPase and plays a central role in neuronal iron trafficking. We have shown that stimulation of glutamate receptors activates neuronal nitric oxide synthase, leading to S‐nitrosylation of Dexras1 and a physiological increase in iron uptake. Here we report that Dexras1 is phosphorylated by protein kinase A (PKA) on serine 253, leading to a suppression of iron influx. These effects were directly associated with the levels of S‐nitrosylated Dexras1, whereby PKA activation reduced Dexras1 S‐nitrosylation in a dose dependent manner. Moreover, we found that adiponectin modulates Dexras1 via PKA. Hence these findings suggest the involvement of the PKA pathway in modulating glutamate‐mediated ROS in neurons, and hint to a functional crosstalk between S‐nitrosylation and phosphorylation. Abstract : PKA phosphorylates Dexras1 on serine 253. PKA phosphorylation of Dexras1 prevents NO‐mediated activation of Dexras1. Adiponectin phosphorylates Dexras1 via PKA.